Acute lymphoblastic leukemia with pregnancy: a rare case - Bhargava, Surbhi; Lal, Manju; Sharma, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Pregnancy complicated with leukemia is rare. Validated data out of which conclusions may be drawn regarding management of pregnancy with leukemia are sparse.